The Role Of Economic Digitalization On Economic Performance In Indonesian - Ratna Arvianti; Muhammad Sri Wahyudi Suliswanto (Universitas Udayana, 2024)
Economic digitalization has an important role in improving the economic performanceof a country. The purpose of this study is to analyze the effect of economic digitalizationas measured by internet users, financial technology, electronic money, and electroniccommerce on economic performance proxied using Gross Regional Domestic Product(GRDP) with a research focus on 34 Indonesian provinces during the 2019-2022 period.The method used in this study is a panel data regression model with secondary datasourced from BPS, OJK, and BI. So the best model is obtained, namely the Fixed EffectModel. Partially, the results showed that the internet users variable had a positive andsignificant effect on GRDP, financial technology had a negative and significant effect onGRDP, electronic money and electronic commerce variables had a negative andinsignificant effect on GRDP. Simultaneously, the variables of internet users, financialtechnology, electronic money, and electronic commerce affect GRDP.